Objective and subjective analysis of women's voice with idiopathic Parkinson's disease - Riviana Rodrigues das Graças; Ana Cristina Côrtes Gama; Francisco Eduardo Costa Cardoso; Bárbara Pereira Lopes; Iara Barreto Bassi (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To compare the voice quality of women with idiopathic Parkinson's disease and those without it. METHODS: An evaluation was performed including 19 female patients diagnosed with idiopathic Parkinson's disease, with an average age of 66 years, and 27 women with an average of 67 years-old in the Control Group. The assessment was performed by computed acoustic analysis and perceptual evaluation. RESULTS: Parkinson's disease patients presented moderate rough and unstable voice quality. The parameters of grade, roughness, and instability had higher scores in Parkinson's disease patients with statistically significant differences. Acoustic measures of Jitter and period perturbation quotient (PPQ) significantly differ between groups. CONCLUSIONS: Parkinson's disease female individuals showed more vocal alterations compared to the Control Group, when both perceptual and acoustic evaluations were analyzed.